Film Dokumenter “Ngantung Ari-Ari” Antara Nalar dan Naluri Dari Tradisi Bali Kuno - I Dewa Made Satria Sitangga Wijaya; I Made - Agus Wirawan; I Gede - Partha Sindu (Universitas Pendidikan Ganesha, 2019)
The purposes of the study were: 1) To develop a documentary film “Ngantung Ari-ari” antara Nalar dan Nalusi dari Tradisi Bali Kuno in Bayunggede village. 2) To find out the response of the people to the final results of the Documentary Film “Ngantung Ari-ari” antara Nalar dan Nalusi dari Tradisi Bali Kuno in Bayunggede VillageThis research was a research and development that used the Cyclic Strategy method, which is a method that uses a looping system at each stage if there are deficiency that determined by testing stage. Data collection techniques were carried out by observation, interviews, literature studies and documentation. This research was implemented using Adobe Premiere Pro CS6 as a video editing application and Adobe After Effect CS 6 as an application for adding effects and animations to videos and using Adobe Audition Pro CS6 as a sound editor.The test was did through several stages, there were the content expert test and media expert test in pre-production, content expert test and media expert test after the production until the audience respondent tests to determine the achievement and quality of the film. For the results of the test the audience respondents get very good results, by the percentage of 96%. After the film was finished, it was hoped that the people understanding of the tradition, both hanging and buried and tolerance between religious people is rising and solve the ongoing conflict. Keywords: Documentery Film, Cyclic Strategy, “ngantung ari-ari”